FAKTOR KESULITAN BELAJAR MATEMATIKA MATERI PERKALIAN KELAS 3B SDI AL- IKHLAS KARANGREJO KABUPATEN TULUNGAGUNG - Iqqlima Nuraida Zensa; Yasip (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning difficulties in students are a reality that is often found in every school. Moreover, in elementary schools, there are still many students who find it difficult to understand multiplication material. According to (Cahyadi, et al. 2021: p. 175) the problem occurs because most students have difficulty understanding the material on multiplication operations. This will result in low student learning outcomes and difficulty in understanding subsequent material. The purpose of this study was to determine the factors of learning difficulties in mathematics multiplication material for class 3b, SDI Al-Ikhlas Karangrejo, Tulungagung Regency. The data collection method used observation, interviews and documentation. While data analysis used descriptive analysis Miles and Huberman which consisted of: Data collection, data reduction, data presentation, and drawing conclusions/verification. The findings of this study prove that the factors of learning difficulties in mathematics multiplication material for class 3b SDI Al-Ikhlas Karangrejo, Tulungagung Regency consist of internal and external factors from students. The results of this study can be used as evaluation material in efforts to improve understanding of multiplication.